2018
DOI: 10.2217/imt-2017-0131
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Aggravates Breast Cancer by Inducing Immunosuppression in the Tumor Bearing Mouse

Abstract: The aim of this approach is to test the effects and related mechanism of vitamin D (VD) treatment on the outcomes of breast cancer. BALB/c mice were injected with 4T1 breast cancer cell suspension. The test group was treated with VD reagent. The survival and tumor size of mice were observed. The proliferation of 4T1 in vitro was detected by MTS analysis. The changes of immune parameters and microenvironment in mice were evaluated by flow cytometry and real-time RT-PCR. Our results demonstrate that VD administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…It should be noted that in our experiment, a calcitriol dose was given on day 7 after the implantation of tumor cells, when tumors became palpable [22], whereas in the experiment conducted by Zhang et al, the treatment was started one day before tumor cell transplantation [23]. Moreover, another study has indicated that the growth of primary 4T1 tumor was accelerated upon calcitriol treatment beginning 17 days after the inoculation of tumor cells [24]. Therefore, it seems that the final effect of calcitriol or cholecalciferol administration may depend on the stage of tumor development when the treatment was initiated.…”
Section: Introductionmentioning
confidence: 77%
“…It should be noted that in our experiment, a calcitriol dose was given on day 7 after the implantation of tumor cells, when tumors became palpable [22], whereas in the experiment conducted by Zhang et al, the treatment was started one day before tumor cell transplantation [23]. Moreover, another study has indicated that the growth of primary 4T1 tumor was accelerated upon calcitriol treatment beginning 17 days after the inoculation of tumor cells [24]. Therefore, it seems that the final effect of calcitriol or cholecalciferol administration may depend on the stage of tumor development when the treatment was initiated.…”
Section: Introductionmentioning
confidence: 77%
“…In parallel, a deficiency of vitamin D in the diet accelerated the rate of tumor growth [14,15], and vitamin D receptor (VDR) ablation further enhanced the tumor volume and metastatic potential [16,17]. On the other hand, our research group recently published a study in which we showed stimulation of metastasis after administration of calcitriol and its analogs in the 4T1 mouse model of breast cancer [9], while Cao et al reported a significant increase in tumor volume after vitamin D treatment [18]. The results of observational studies and randomized clinical trials (RCTs) are not conclusive and indicate a lack or only small benefits of vitamin D supplementation in breast cancer pathogenesis [19,20].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, in the model of the 4T1 mouse mammary gland cancer transplanted subcutaneously, Cao et al have shown, that vitamin D stimulated the growth of primary tumors and decreased survival time of mice. The authors correlated this unfavorable effect with decreased Th1 response and increased recruitment of myeloid-derived suppressor cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%